Assessment of public service broadcasting - Picard, Robert G. (Javnost (Ljubljana), 2003)
This article discusses the rationale and purposes of the expanding assessment of public service broadcasting from the perspectives of performance evaluationin public administration and media management. The author argues that increased assessment of public broadcasters is part of a movement toward better oversight of a range of public social services that is designed to improve service effectiveness. The article explores economic and managerial approaches to assessment that are increasingly augmenting traditional content and audience assessment practices in public broadcasting. It introduces and illustrates a variety of types of economic and managerial measures that provide insight into the operations and effectiveness of public service broadcasters and explores what they reveal to assessors and managers and the implications of those measures.
Keywords: mass media; množični mediji; radio; television; televizija; management; kvaliteta; vodenje; poslovna uspešnost; efficiency; učinkovitost